(3fXe eSGfOI GdbQGQGJ HGYJeGO GdHQeLjI GdLGgRI (B/s - (3GdWGFj, eMeO YHO MSjfs ((3YeGf(B: s (3OGQ hGFd(B, s, 2008)
(3fXe eSGfOI GdbQGQGJ (B: (3GdfThA h Gdeaghe h GdNUGFU , CfhGY fXe eSGfOI GdbQGQGJ h COhGJgG h JWHjbGJgG , GdGfXeI GdaQYjI dfXe eSGfOI GdbQGQGJ , eOGNd JWhjQ h eQGMd JUeje h HfGA fXe eSGfOI GdbQGQGJ , OhQ fXe eSGfOI GdbQGQGJ aj UfY GdbQGQGJ GdGOGQjI , cjajI GYJeGO JWHjbGJ fXe eSGfOI GdbQGQGJ(B.s
(3eQGLY U(B.229s
Keywords: (3GJNGP GdbQGQGJs; (3EOGQI GdGYeGds; (3GdbQGQGJ GdGOGQjIs